1994
DOI: 10.1007/bf01623238
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measurement of regional and whole body bone mass in young healthy adults

Abstract: The so-called peak bone mass (PBM) represents the highest amount of bony tissue achieved during life at a given site of the skeleton. It has been suggested that PBM might be achieved as late as the fourth decade, but recent data have indicated that PBM is already achieved by the end of sexual maturation, namely at the end of the second decade. The solving of this apparent controversy is of interest for a better understanding of bone homeostasis and for defining the cohort of normal subjects to be evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 18 publications
5
37
1
1
Order By: Relevance
“…The coefficient of variation of DXA was 1-2% or less for regional BMD as well as for WB-BMC measurements [9,10]. Bone mass values at baseline were expressed as percentages of peak bone masses in sex-matched young healthy adults, which were: LS BMD 1.07±0.10 and 1.06±0.13 g·cm -2 ; FN BMD 0.90±0.11 and 0.96±0.15 g·cm -2 ; FS BMD 1.73±0.17 and 2.02±0.13 g·cm -2 ; WB BMC, 2259±248 and 2573±327 g·m -1 ×1.70 (mean±SD), in females and males, respectively [9,10]. Bone mass changes during follow-up were expressed as percentage difference from baseline.…”
Section: Bone Mass Measurementmentioning
confidence: 91%
“…The coefficient of variation of DXA was 1-2% or less for regional BMD as well as for WB-BMC measurements [9,10]. Bone mass values at baseline were expressed as percentages of peak bone masses in sex-matched young healthy adults, which were: LS BMD 1.07±0.10 and 1.06±0.13 g·cm -2 ; FN BMD 0.90±0.11 and 0.96±0.15 g·cm -2 ; FS BMD 1.73±0.17 and 2.02±0.13 g·cm -2 ; WB BMC, 2259±248 and 2573±327 g·m -1 ×1.70 (mean±SD), in females and males, respectively [9,10]. Bone mass changes during follow-up were expressed as percentage difference from baseline.…”
Section: Bone Mass Measurementmentioning
confidence: 91%
“…These measurements allow the determination of bone mineral content and soft tissue mass on a pixel-per-pixel basis. Then, the soft tissue mass is partitioned into fat and nonfat lean body mass by a calibration procedure based on the attenuation of the soft tissue outside the bone and the attenuation of an external dedicated phantom [29,30]. The advantage is that the method permits, in a few minutes, the derivation of the total FM directly rather than by subtracting the other body compartments [4].…”
Section: Dual-energy X-ray Absorptiometrymentioning
confidence: 99%
“…The advantage is that the method permits, in a few minutes, the derivation of the total FM directly rather than by subtracting the other body compartments [4]. The reproducibility of the measurements is [4,29,32,33]. An advantage of DXA over hydrodensitometry, total body potassium and water dilution is that it can provide information about the composition of body segments and muscle mass and the distribution of fat between trunk and limbs [34].…”
Section: Dual-energy X-ray Absorptiometrymentioning
confidence: 99%
“…Longitudinal studies in young men (20±35 y), who had up to 10haweek physical activity, showed no variation in lumbar spine, proximal femur and whole body BMD after one year (Slosman et al, 1994). On the other hand, young women (aged 20 ± 30 y) who had been training in muscle building activities for at least 1haweek during a 2±5 y period showed a higher lumbar BMD when compared to sedentary women (Rauce et al, 1990).…”
Section: Discussionmentioning
confidence: 99%